2018
DOI: 10.1042/bsr20181059
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the nucleocapsid protein of Middle East respiratory syndrome coronavirus up-regulates CXCL10

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) causes respiratory diseases in humans and has a high mortality rate. During infection, MERS-CoV regulates several host cellular processes including antiviral response genes. In order to determine if the nucleocapsid protein of MERS-CoV (MERS-N) plays a role in viral–host interactions, a murine monoclonal antibody was generated so as to allow detection of the protein in infected cells as well as in overexpression system. Then, MERS-N was stably overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…Its function involves entering the host cells, binding to the viral RNA genome and forms the ribonucleoprotein core to facilitate its replication and process the virus particle assembly and release 27 . Previous reports showed that the N protein from SARS-CoV and MERS-CoV were highly inflammatory nature to promote the expression of inflammatory cytokines, chemokines, prothrombinase and were able to induce acute lung inflammation in mouse model [28][29][30] . The N protein from hantavirus Andes virus increased basal endothelial cell permeability by activating RhoA signaling 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Its function involves entering the host cells, binding to the viral RNA genome and forms the ribonucleoprotein core to facilitate its replication and process the virus particle assembly and release 27 . Previous reports showed that the N protein from SARS-CoV and MERS-CoV were highly inflammatory nature to promote the expression of inflammatory cytokines, chemokines, prothrombinase and were able to induce acute lung inflammation in mouse model [28][29][30] . The N protein from hantavirus Andes virus increased basal endothelial cell permeability by activating RhoA signaling 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In another in vitro study [ 157 ], it was seen that SARS-CoV infection could activate the chemokines of lung traffic, IL8 and IL17, through TLR9, which would cause symptoms and also monocyte-macrophage activation and coagulation upregulation. In a study on MERS-CoV, Aboagye et al [ 158 ] showed that virus nucleocapsid causes an overexpression of antiviral genes, namely, TNF, IL6, IL8, and CXCL10, whose expression is stable over time. The pathogenesis of SARS-CoV-2 damage is still unknown, but unlike other SARS, SARS-CoV-2 shows an initial increase of the Th2 cytokines IL-4 and IL-10 which suppress inflammation [ 51 ] and balance the Th1 hyper-response.…”
Section: Sars-cov-2: Inflammation and Lung Diseasementioning
confidence: 99%
“…Furthermore, several reports suggest that the severe acute respiratory syndrome coronavirus (SARS-CoV) N protein functions as an immune evasion protein and an antagonist of the host interferon response [35,36,37]. Recently, the overexpression of MERS-CoV N in human A549 cells was found to be linked to an up-regulation of antiviral host gene expression including the synthesis of the inflammatory chemokine CXCL10 [38]. Despite this possible immune modulatory activity, SARS-CoV N-specific immune responses are reported to be long-lived and more broadly reactive when compared to SARS-CoV S-specific immunity [39].…”
Section: Introductionmentioning
confidence: 99%